Becoming a Maker Teacher: Designing Making Curricula That Promotes Pedagogical Change - Becker, Sandra; Jacobsen, Michele (Frontiers in Education, 2020)
In this article, we focus on the case of a Canadian teacher and her students who engaged with a researcher in a year-long design-based research study exploring the implementation of curriculum within a makerspace context. Together, the grade six teacher and researcher co-designed, co-enacted, and co-reflected on three curricular making cycles, one related to sky science, another to mathematical transformations, and a third focused on core concepts of democratic systems. The two-fold purpose of this DBR was to promote pedagogical change through designs for making and to articulate design principles that could be utilized when engaging with curriculum for making. Findings show that the makerspace as learning environment and design-based research as methodology provided a double helix scaffold that compelled the teacher to reconsider her frame when enacting curriculum. For this teacher, collaboration on design-based research and designs for learning in the makerspace promoted a shift in pedagogy and led her and her students to rethink notions of curriculum while questioning what is important to know. An expansion of the intervention to engage multiple teachers in multiple sites to determine scalability is recommended. Study findings point to the makerspace as a promising design frame for rethinking curriculum and pedagogical practice.